Music and War in the United States
1 online resource (342 pages)
Keywords: Music and War in the United States introduces students to the long and varied history of music's role in war. Spanning the history of wars involving the United States from the American Revolution to the Iraq war, with contributions from both senior and emerging scholars, this edited volume brings together key themes in this vital area of study. The intersection of music and war has been of growing interest to scholars in recent decades, but to date, no book has brought together this scholarship in a way that is accessible to students. Filling this gap, the chapters here address topics such as military music, commemoration, music as propaganda and protest, and the role of music in treating post-traumatic stress disorder (PTSD), enabling readers to come to grips with the rich and complex relationship between one of the most essential arts and the conflicts that have shaped American society.